The graphicalization of description: drawing and photography in the fieldwork journals and museum work of Henry Balfour - Morton, C (Royal Anthropological Institute, 2017)
This article considers the fluid interchange between drawing and photography in the work of the first curator of the University of Oxford’s Pitt Rivers Museum, Henry Balfour (1863–1939). By examining in detail two 1920s fieldwork journals compiled by Balfour in Northeast India and East Africa, the article discusses the complementary and differentiated use of drawing and photography by Balfour in the field as well as in the more formal journal document. Moving beyond, the article examines Balfour’s approach to visual evidence more broadly, situating him in the context of his training in natural sciences in the 1880s, as well as wider nineteenth-century anthropological understandings of the relationship between textual, artistic, and photographic data gathering and presentation in the museum setting.